Global Warming Effect to Our Green Earth: Exploring the impact of greenhouse gases on global warming and climate change (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Global warming and climate change refer to an increase in average global temperatures. Natural events and human activities are believed to be contributing to an increase in average global temperatures. This is caused primarily by increases in “greenhouse” gases such as Carbon Dioxide (CO2). It is being clear that human activities have caused most of the century’s warming by releasing heat-trapping gases-called greenhouse gases into the atmosphere. In the present study, an attempt has been made to develop an empirical model and study the empirical aspects of the global climate change by applying the mass energy concept to the earth atmosphere system, assuming that the atmosphere is in hydrostatic balance. Further, we assumed that the earth atmosphere system behaves as a black body. The presence of the gas in the atmosphere keeps some of the radiant energy received by the earth from being returned to space, thus producing the so-called greenhouse effect. The results of the study pointed out that the global temperature changes due to mass increase as a whole of the earth atmosphere system for the period 1900-2050. These changes in global warming are due to temperature increases from 0.053oC to 0.84oC. The predicted changes are in good agreement with the observed global warming (IPCC, 1990). The temperature changes due to doubling of CO2 are only 0.02oC by 2050. The global warming due to temperature changes may be attributed to increase in mass as a whole including greenhouse gases (CO2, water vapor, particulate and other CFC’s) and human activity and feedbacks.